EFFECT OF EMPOWERMENT AND CHARACTERISTICS OF WORKING WITH JOB SATISFACTION AS MOTIVATION OF MEDIATION (Study On PD. Bank Perkreditan Rakyat BKK Taman Kabupaten Pemalang) - Khusnul Amalia, 1352020015 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study was to investigate the factors that influence job satisfaction and employee motivation in PD. Bank Perkreditan Rakyat BKK Taman Kabupaten Pemalang. The purpose of this research is the Test and analyze the effect of empowerment on employee motivation. Examine and analyze the effect of job characteristics on employee motivation. Examine and analyze the effect of empowerment on job satisfaction. Examine and analyze the effect of job characteristics on job satisfaction. Examine and analyze the effect of motivation on job satisfaction. The population in this study are all permanent employees in Bank Perkreditan Rakyat BKK Taman Kabupaten Pemalang. Data population of 111 people. The sampling technique used in this study is a sampling technique Census. Of the total population of 111 people we took a sample of 100% of the entire population so that the sample size in this study as many as 111 people. The analysis tool used is regression analysis. Key words : Empowerment, Job characteristics, motivation and job satisfaction